Radiological diagnosis of canine dirofilariosis in case of parasitization by Dirofilaria immitis - Yevstafieva, V.; Kryvoruchenko, D. (Scientific Progress & Innovations, 2022)
Radiography is a widespread examination in veterinary medicine, which can be used to study the structure, size, condition, and location of various organs. This diagnostic method is also used to detect pathology of the chest cavity organs - lungs and heart. Among the instrumental methods of diagnosis of dirofilariosis in dogs caused by parasitization of Dirofilaria immitis, in modern veterinary medicine, chest radiography is an additional method that allows for establishing the degree of invasion and the development of the pathological process in the body of sick animals. The aim of the research was to find out the informativeness of the use of radiography in diagnostic studies in the case of parasitization in dogs by D. immitis. The results of radiological examinations of the thoracic cavity organs of dogs indicate that at the intensity of microfilarial infection up to 20 larvae/cm3, there were no pathological changes. At the intensity of infestation of 20–40 larvae/cm3, dilatation of the heart (left atrium, right atrium, and ventricle), dilation of the main trunk of the pulmonary artery and alveolar darkening were found in 11.1 % of the experimental dogs. At the same time, 22.2 % of dogs showed interstitial lung darkening, and 33.3 % – thickening of the bronchial walls. At the intensity of microfilarial infestation of 40–60 larvae/cm3, changes were observed on the radiographs of sick dogs, characterized by: 55.5 % – bronchial type opacification, 44.4 % – alveolar type opacification and pulmonary artery dilation, in 33.3 % – dilation of the lungs and right heart vessels, interstitial type opacification, in 22.2 % – left atrial dilation, hydrothorax, and collapse of the main bronchi. At the intensity of infestation of more than 60 larvae/cm3 in 100 % of dogs dilatation of pulmonary vessels, in 77.8 % – bronchial and interstitial type lung opacification, collapse of the main bronchi, in 66.7 % – dilatation of the right heart, in 44.4 % – alveolar type opacification, in 33.3 % – hydrothorax, in 22.2% – dilatation of the left atrium were found. The obtained results prove the high informative value of radiological examination of dogs in the presence of heartworm disease caused by D. immitis parasitization. This makes it possible to effectively establish the diagnosis, as well as to have an in-depth understanding of the animal's condition, and allows you to adjust the treatment.